Income shocks and HIV in Sub-Saharan Africa - Burke, Marshall; Gong, Erick; Jones, Kelly M. (International Food Policy Research Institute, 2011)
Poverty is commonly cited as a key driver of the HIV/AIDS epidemic, yet little causal evidence exists linking economic conditions to actual disease outcomes. Using data on more than 200,000 individuals across 19 Sub-Saharan African countries, we present evidence that negative income shocks can lead to substantial increases in HIV prevalence, particularly for women in rural areas. Building on recent work showing that income shortfalls can induce some women to engage in higher-risk sex, we match data on individuals' HIV status from the Demographic and Health Surveys to data on recent variation in local rainfall, a primary (and exogenous) source of variation in income for rural households in Africa. We find that infection rates for women (men) in HIV-endemic rural areas increase significantly by 14 percent (11 percent) for every drought event experienced in the previous 10 years. Further analysis suggests that women most affected by the shocks (that is, those engaged in agriculture) are driving the women's results; these women are partnering with men least affected (those employed outside agriculture). Our findings suggest a role for formal insurance and social safety nets in tackling the HIV/AIDS epidemic.